DIMENSI RESIKO OPERASIONAL TERHADAP RETURN ON ASSET (ROA) PADA BANK SYARIAH YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) PERIODE TAHUN 2015 – 2017 - Siti Hayati Efi Friantin (STIE AUB Surakarta, 2019)
This study aims to examine the effect of Dimentiont Operational Risks ( Non Performing Financing (NPF), Operational Cost per Operating Income (BOPO), and Financing to Deposit Ratio (FDR)) to Return On Assets (ROA) as a proxy of profitability of Sharia Commercial Bank in Indonesia period 2015-2017. The data used in this research is obtained from the Annual Sharia Bank Annual Sharia Financial Statement data for period 2015-2017. The population in this study are 12 Sharia Commercial Banks in Indonesia. The analytical technique used in this research is multiple linear regression that aims to obtain a comprehensive description of the relationship between variables. While the classical assumptions used in this study include the autocorrelation test, ujinormalitas, multicolonierity test, and heteroscedasticity test. The results showed that the NPF has a negative effect is not significant to ROA.Sedangkan BOPO and FDR variables have positive and significant impact on ROA Syariah Commercial Bank. The results of this study is expected to be a guide for the management of Sharia Commercial Bank in managing the company. The value of Adjusted R-Square in regression model is 0.352 which shows the ability of independent variable that is Non Performing Financing (NPF), Operational Expense per Oprasional (BOPO) and Financing to Deposite Ratio (FDR) in explaining the dependent variable that is profitability of company Return On Asset (ROA) is 35.2% while the rest of 64.8% described other variables that are not included in the study.